Minutes of the 118th meeting of BRAC University new campus development committee - Brac University (Brac University, 2023)
The 118th meeting of BRAC University Campus Development Committee was held at 10:30 a.m. on 02 April 2018 with Mr. A.S.M. Rashidul Hai, Project Director, BRACU New Campus project in the chair. The chair welcomed all participants and commenced the business of the meeting.